3D shape of Orion A with Gaia DR2 An informed view on Star Formation Rates and Efficiencies. Issue Volume 14:Issue S345(2019) (August 2018) - Großschedl, Josefa E.; Alves, João; Meingast, Stefan; Hasenberger, Birgit
Abstract: The giant molecular cloud Orion A is the closest massive star-forming region to earth ( d ∼ 400 pc). It contains the rich Orion Nebula Cluster (ONC) in the North, and low-mass star-forming regions (L1641, L1647) to the South. To get a better understanding of the differences in star formation activity, we perform an analysis of the gas mass distribution and star formation rate across the cloud. We find that the gas is roughly uniformly distributed, while, oddly, the ONC region produced about a factor of ten more stars compared to the rest of the cloud. For a better interpretation of this phenomenon, we use Gaia DR2 parallaxes, to analyse distances of young stellar objects, using them as proxy for cloud distances. We find that the ONC region indeed lies at about 400 pc while the low-mass star-forming parts are inclined about 70 ∘ from the plane of the sky reaching until ∼470 pc. With this we estimate that Orion A is an about 90 pc long filamentary cloud (about twice as long as previously assumed), with its "Head" (the ONC region) being "bent" and oriented towards the galactic mid-plane. This striking new view allows us to perform a more robust analysis of this important star-forming region in the future.